Peptidoglycan of Staphylococcus aureus Upregulates Monocyte Expression of CD14, Toll-Like Receptor 2 (TLR2), and TLR4 in Human Blood: Possible Implications for Priming of Lipopolysaccharide Signaling - Hadley, J. S. (American Society for Microbiology, 2005)
Previous studies have indicated that peptidoglycan (PepG) from gram-positive bacteria can exert a priming effect on the innate immune response to lipopolysaccharide (LPS) from gram-negative bacteria. Here, we hypothesized that this priming effect may be preceded by enhanced expression of monocyte CD14, Toll-like receptor 2 (TLR2), and TLR4. In an ex vivo whole human blood model, we observed a substantial synergy between LPS and PepG in the release of tumor necrosis factor alpha and interleukin-1β (IL-1β) over the 24-h experimental period, whereas the effect on IL-8 and IL-10 release was more time dependent. The priming effect of PepG on cytokine release was preceded by a rapid upregulation of CD14, TLR2, and TLR4 expression on monocytes: at 3 hours there was a twofold increase in CD14 expression (P < 0.03), a fivefold increase in TLR2 expression (P < 0.03), and a twofold increase in TLR4 expression (P < 0.03). CD14 and TLR2 remained upregulated throughout the experimental period following exposure to PepG (P < 0.05). Only a transient upregulation of these monocyte receptors was observed following treatment with LPS or LPS plus PepG. In conclusion, the synergistic effect of LPS and PepG on cytokine release is preceded by a reciprocal upregulation of TLR2 and TLR4 by both bacterial cell wall components.